2010
DOI: 10.1890/es10-00073.1
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback between microclimate and shrub encroachment in the northern Chihuahuan desert

Abstract: Abstract. Woody plant encroachment is affecting vegetation composition in arid grasslands worldwide and has been associated with a number of environmental drivers and feedbacks. It has been argued that the relatively abrupt character (both in space and in time) of grassland-to-shrubland transitions observed in many drylands around the world might result from positive feedbacks in the underlying ecosystem dynamics. In the case of the Chihuahuan Desert, we show that one such feedback could emerge from interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 29 publications
8
128
1
Order By: Relevance
“…Shrub encroachment can affect the land surface albedo, emissivity, and roughness with important impacts on the near surface climate (Beltran-Przekurat et al, 2008). Even though in some cases changes in albedo are negligible, the increase in soil energy storage at encroached area can modify the microclimate with a positive feedback on vegetation (D'Odorico et al, 2010c;He et al, 2010). Recent regional climate modeling activities that seek to change the boundary conditions of the surface state may provide some insight into the influence and strength of land-atmosphere couplings as a response to changing surface conditions.…”
Section: The Effects On Regional Hydrological Processesmentioning
confidence: 99%
“…Shrub encroachment can affect the land surface albedo, emissivity, and roughness with important impacts on the near surface climate (Beltran-Przekurat et al, 2008). Even though in some cases changes in albedo are negligible, the increase in soil energy storage at encroached area can modify the microclimate with a positive feedback on vegetation (D'Odorico et al, 2010c;He et al, 2010). Recent regional climate modeling activities that seek to change the boundary conditions of the surface state may provide some insight into the influence and strength of land-atmosphere couplings as a response to changing surface conditions.…”
Section: The Effects On Regional Hydrological Processesmentioning
confidence: 99%
“…Similar to trees, shrubs provide shade and windbreaks that increase soil humidity, allowing other plants to flourish in these areas [18]. It has been demonstrated, for example, that in arid areas with little cloud cover, shrubs can produce microclimate conditions that are up to 20 °C cooler than the surrounding bare ground, as well as having lowered rates of evaporation and increased soil humidity [58]. This creates an area with decreased evapotranspiration, increased humidity and better growing conditions for grasses and sedges [21].…”
Section: Shrubs Vs Treesmentioning
confidence: 99%
“…Further, a review of the use of shrubs as nursery plants found that shrubs were most effective in drier, sunnier areas than in wetter, shaded areas [19]. As some shrubs are larger than others, microclimate changes could also be exploited by farmers who would be able to plant crops beneath the shrubs and in the windbreak that they create, with such crops requiring decreased irrigation compared to crops fully exposed to the wind and sun [58].…”
Section: Shrubs Vs Treesmentioning
confidence: 99%
“…Positive feedbacks have been shown to increase the rate and extent of woody encroachment in many grasslands (Schlesinger et al 1990, Van Auken 2000, Scheffer et al 2001, Wookey et al 2009, D'Odorico et al 2010). However, the study of encroachment feedbacks has focused primarily on semi-arid and arctic grasslands (Archer et al 1988, Schlesinger et al 1990, Ravi et al 2007, Wookey et al 2009, D'Odorico et al 2010, with examples in mesic systems restricted to theoretical models (D'Odorico et al 2006, Baudena et al 2010. This study addresses the potential for positive feedback mechanisms in mesic tallgrass prairie, a system in which positive feedbacks have not been previously identified.…”
Section: Introductionmentioning
confidence: 99%
“…In semi-arid and arctic grasslands, woody encroachment alters temperature and/or the availability of water and nutrients, which facilitates the establishment of other shrubs and creates a positive feedback loop (Schlesinger et al 1990, Scheffer et al 2001, Ravi et al 2007, Wookey et al 2009, D'Odorico et al 2010; see Archer et al 1988 for mechanisms related to seed dispersal). However, these and other mechanisms have been found to have a minimal impact on encroachment of tallgrass prairie (Briggs et al 2005, McKinley andBlair 2008).…”
Section: Introductionmentioning
confidence: 99%